A harmonized segmentation protocol for hippocampal and parahippocampal subregions: Why do we need one and what are the key goals?. Issue 1 (15th November 2016) - Wisse, Laura E.M.; Daugherty, Ana M.; Olsen, Rosanna K.; Berron, David; Carr, Valerie A.; Stark, Craig E.L.; Amaral, Robert S.C.; Amunts, Katrin; Augustinack, Jean C.; Bender, Andrew R.; Bernstein, Jeffrey D.; Boccardi, Marina; et al.
ABSTRACT: The advent of high‐resolution magnetic resonance imaging (MRI) has enabled in vivo research in a variety of populations and diseases on the structure and function of hippocampal subfields and subdivisions of the parahippocampal gyrus. Because of the many extant and highly discrepant segmentation protocols, comparing results across studies is difficult. To overcome this barrier, the Hippocampal Subfields Group was formed as an international collaboration with the aim of developing a harmonized protocol for manual segmentation of hippocampal and parahippocampal subregions on high‐resolution MRI. In this commentary we discuss the goals for this protocol and the associated key challenges involved in its development. These include differences among existing anatomical reference materials, striking the right balance between reliability of measurements and anatomical validity, and the development of a versatile protocol that can be adopted for the study of populations varying in age and health. The commentary outlines these key challenges, as well as the proposed solution of each, with concrete examples from our working plan. Finally, with two examples, we illustrate how the harmonized protocol, once completed, is expected to impact the field by producing measurements that are quantitatively comparable across labs and by facilitating the synthesis of findings across different studies. © 2016 Wiley Periodicals, Inc.